A study on Infant Feeding practices among mothers of a Rural hilly area of District Dehradun - Vyas, Shaili (Bangladesh Journal of Medical Science, 2016)
Background: Optimal infant and young child-feeding (IYCF) practices are crucial for nutritional status, growth, development, health, and ultimately the survival of infants and young children. Practices like premature cessation of breastfeeding, early and unnecessary introduction of top feeding in incorrect dilutions and unhygienic pattern are also quite prevalent in many communities thereby aggravating malnutrition in children. The present study was undertaken to assess the feeding practices in the first six months among children less than three years, to know the barriers for the same and to study the effect of feeding practices on their nutritional status. Methodology: A cross sectional study was conducted in all the villages under Rural Health Training Centre, the field practice area of Department of Community Medicine. A total of 500 mothers with their under three children were included in the study. A Predesigned pretested semi structured questionnaire was used to collect information on feeding practices within the first six months of life. Results: In the present study a total of 160 (33%) children were on top milk of which majority consumed cows milk and were fed by bottle (91%). Majority of the mothers diluted milk (87.5%) in the proportion of 1:1 (38%). In appropriate feeding practices were more common males. Infants who had inappropriate feeding practices in the initial six months were found to be maximally undernourished. Conclusion: The present study revealed suboptimal feeding practices in the first six months, which was again found as one of the major risk factor for malnutrition among children. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.103-110